Iron Man : 3-movie collection [videorecording (Blu-Ray)] - Favreau, Jon; Downey, Robert, Jr., 1965-; Howard, Terrence; Bridges, Jeff, 1949-; Paltrow, Gwyneth, 1972-; Bettany, Paul, 1971-; Cheadle, Don; Johansson, Scarlett, 1984-; Rourke, Mickey; Rockwell, Sam; Black, Shane; Kingsley, Ben, 1943-; et al. (Marvel Studios, 2017)
Iron Man: When wealthy industrialist Tony Stark is forced to build an armored suit after a life-threatening incident, he ultimately decides to use its technology to fight against evil.